Peran Pendidikan Agama Islam dalam Memerangi Intoleransi dan Ekstremisme di Indonesia - Latifah, Nur (MODELING: Jurnal Program Studi PGMI, 2024)
Islamic religious education plays a very important role in shaping the character of Muslims and preventing the spread of intolerance and extremism in Indonesia. The country of Indonesia, which is known for its diversity, faces big challenges in maintaining harmony between religious communities, especially related to the emergence of radical ideologies which often use the name of religion. This research aims to examine the role of Islamic religious education in fighting intolerance and extremism in Indonesia. It is hoped that the moderation approach (wasathiyah) in Islamic religious education can be a solution to overcome beliefs that lead to violence and injustice. Religious education based on peaceful Islamic teachings and respect for diversity can help the younger generation to avoid exclusive and radical attitudes. Apart from that, it is hoped that the integration of Pancasila values ??in Islamic religious education can strengthen the sense of nationality and strengthen commitment to tolerance between religious communities. Through good education, religious teachers have a key role in instilling attitudes of tolerance and moderation, as well as guiding students to understand religious teachings correctly. This research concludes that moderate Islamic religious education, based on the Islamic values ??of rahmatan lil-alamin, is very important to prevent radicalization and promote a peaceful, harmonious and inclusive life in Indonesia. Abstrak Pendidikan agama Islam memainkan peran yang sangat penting dalam membentuk karakter umat Muslim dan mencegah penyebaran intoleransi serta ekstremisme di Indonesia. Negara Indonesia, yang dikenal dengan keberagamannya, menghadapi tantangan besar dalam menjaga harmoni antarumat beragama, terutama terkait dengan munculnya paham radikal yang sering kali mengatasnamakan agama. Penelitian ini bertujuan untuk mengkaji peran pendidikan agama Islam dalam memerangi intoleransi dan ekstremisme di Indonesia. Pendekatan moderasi (wasathiyah) dalam pendidikan agama Islam diharapkan dapat menjadi solusi untuk menanggulangi paham-paham yang mengarah pada kekerasan dan ketidakadilan. Pendidikan agama yang berbasis pada ajaran Islam yang damai dan menghargai keberagaman dapat membantu generasi muda untuk menghindari sikap eksklusif dan radikal. Selain itu, integrasi nilai-nilai Pancasila dalam pendidikan agama Islam diharapkan dapat memperkuat rasa kebangsaan dan memperkuat komitmen terhadap toleransi antarumat beragama. Melalui pendidikan yang baik, guru agama memiliki peran kunci dalam menanamkan sikap toleransi dan moderasi, serta membimbing siswa untuk memahami ajaran agama secara benar. Penelitian ini menyimpulkan bahwa pendidikan agama Islam yang moderat, berbasis pada nilai-nilai Islam yang rahmatan lil-alamin, sangat penting untuk mencegah radikalisasi dan mempromosikan kehidupan yang damai, harmonis, dan inklusif di Indonesia.